2013
DOI: 10.3201/eid1902.120527
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Outbreak in a Primary School, Milan, Italy

Abstract: Investigation of an outbreak of tuberculosis (TB) in a primary school in Milan, Italy, found 15 schoolchildren had active TB disease and 173 had latent TB infection. TB was also identified in 2 homeless men near the school. Diagnostic delay, particularly in the index case-patient, contributed to the transmission of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 7 publications
2
23
0
1
Order By: Relevance
“…Most pre-college students have great academic pressure due to the nationwide college entrance examinations and the lack of physical exercise in China. Numerous previous relevant literatures reported crowded living, insufficient ventilation, persistent contact with tuberculosis cases and diagnostic delay as the primary factors causing pulmonary tuberculosis outbreaks among high school students [11, 21, 22]. Our results showed that students who resided in the same class as the index case were at a significantly higher risk than other students.…”
Section: Discussionsupporting
confidence: 44%
“…Most pre-college students have great academic pressure due to the nationwide college entrance examinations and the lack of physical exercise in China. Numerous previous relevant literatures reported crowded living, insufficient ventilation, persistent contact with tuberculosis cases and diagnostic delay as the primary factors causing pulmonary tuberculosis outbreaks among high school students [11, 21, 22]. Our results showed that students who resided in the same class as the index case were at a significantly higher risk than other students.…”
Section: Discussionsupporting
confidence: 44%
“…Indeed, TB outbreaks in schools are relatively common (e.g. [10]), and both schools and workplaces are important settings for screening potential contacts of index cases [9]. The population in the model is spatially distributed according to estimates of the population density [11] over 219 square cells covering the state territory.…”
Section: Methodsmentioning
confidence: 99%
“…This is of particular importance for diseases diffused in marginalized parts of the population that may have little access to Internet, and that in any case are not exchanging information with people belonging to other social classes, but that may nonetheless be part of their "physical" neighborhood, for instance by commuting together, or meeting at work, etc. Just as an example, a person living in Europe or USA rarely considers the possibility of contracting tuberculosis, which is indeed rather a rare disease [19] but may cause sudden outbreaks in specific areas [20].…”
Section: Discussionmentioning
confidence: 99%